A Smart Pill Reminder with Configurable Alerts, Multi-Modal Notifications, and Integrated Health Monitoring for Medical Adherence - Mohanty, Chandana; S., Saranya; S., Carolina Jennifer; Raj, Remya (Journal of ISMAC, 2025)
Patients must frequently follow medication regimens that call for both large dosages and extended durations of time until the recommended course is finished in order to recover from hospitalization and the diagnosis. Medication adherence is the ability of the patient to adapt to changes in medication as the disease progresses, as well as the patient's dedication to taking their medications on time and finishing the entire course of treatment. In particular, elderly patients with complex conditions like Alzheimer's, dementia, diabetes, and liver diseases require continuous and long-term medication adherence, making it difficult to maintain strict adherence to prescribed treatments and the medication list provided by healthcare professionals. Disease progression, higher healthcare expenses, and higher death rates can result from non-adherence. Disease progression, higher healthcare expenses, and higher death rates can result from non-adherence. 53% of medication errors happened during administration, and 17% were related to prescription errors, according to a study done at a tertiary care hospital in South India. Forgetting, not being aware, and having trouble handling complicated prescriptions are all contributing factors.We suggest a smart pill reminder system as a creative and portable way to help patients stick to a regular medication schedule in order to overcome these difficulties. This system's main goal is to improve adherence by sending out timely reminders, which will cut down on missed doses and guarantee appropriate medication intake. The reminder system provides a workable way to enhance patient outcomes and the overall effectiveness of healthcare by instituting a methodical approach to medication management. Patients or caregivers can personalize medication names and dosage schedules via a dedicated webpage. Along with providing real-time data on environmental variables like temperature and humidity, as well as vital signs like heart rate and SpO2 levels, this platform also makes it possible to track a patient's history of medication intake.
Keywords: Medicine Box; Medical Adherence; Dementia; Medication Scheduling; Webpage Integration; IR Sensors